DEVELOPMENT OF FARMING AND HOUSEHOLDS - Ochilova Nargiza Akramovna (Web of Journals Publishing, 2025)
The article highlights issues related to the development of dekhkan and subsidiary farms in the field of agriculture and ways to effectively organize their activities, as well as an innovative approach to the production of agricultural products, factors affecting the strengthening of the export potential of the sector.
Keywords: Agriculture, farming, horticulture, productivity, efficiency, agricultural products, innovative agricultural technologies.